2009
DOI: 10.1093/mp/ssp023
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PIN Genes in Rice ( Oryza sativa L.): Tissue Specificity and Regulation by Hormones

Abstract: Twelve genes of the PIN family in rice were analyzed for gene and protein structures and an evolutionary relationship with reported AtPINs in Arabidopsis. Four members of PIN1 (designated as OsPIN1a-d), one gene paired with AtPIN2 (OsPIN2), three members of PIN5 (OsPIN5a-c), one gene paired with AtPIN8 (OsPIN8), and three monocot-specific PINs (OsPIN9, OsPIN10a, and b) were identified from the phylogenetic analysis. Tissue-specific expression patterns of nine PIN genes among them were investigated using RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
232
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(250 citation statements)
references
References 29 publications
18
232
0
Order By: Relevance
“…The auxin efflux carrier gene family, PIN-formed (PINs), is the key factor for auxin polar transport (Petrásek et al 2006;Wang et al 2009). PIN gene expression may represent auxin accumulation level (Xu et al 2006;Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxin efflux carrier gene family, PIN-formed (PINs), is the key factor for auxin polar transport (Petrásek et al 2006;Wang et al 2009). PIN gene expression may represent auxin accumulation level (Xu et al 2006;Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PIN gene expression may represent auxin accumulation level (Xu et al 2006;Huang et al 2010). OsPIN1 is detected in rice calli (Xu et al 2006) and is related to organogenesis Wang et al 2009). Similarly, B-type response regulator (B-RR) proteins are positive signal regulators for cytokinin signaling (Müller and Sheen 2007) and the expression level of B-RR gene can be representive of endogenous cytokinin level (Mason et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional responses of plant hormones have been analyzed at individual gene, gene family and whole genome levels in many plant species. [2][3][4][5][6][7][8][9][10][11] Based on gene expression and genetic studies in loss-of-function mutants, several genes involved in common signaling pathways of two or more hormones have also been identified and extensive crosstalk and signal integration has been uncovered. [12][13][14][15] Various genetic analyses suggested that hormones work via distinct pathways to elicit their responses.…”
Section: Introductionmentioning
confidence: 99%
“…There are twelve PIN genes present in rice and eight PIN genes in found Arabidopsis thaliana (Blilou et al 2005;Wang et al 2009a). PIN genes shows distinct pattern of cellular and sub-cellular localization in root and shoot and shows tissue specific expression Blilou et al 2005;Paponov et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…AtPIN1 localizes polarly in plasma membrane, and upon pharmacological disruption, it immediately relocalizes, suggesting conceptual basis of auxin flux affects tropic response and patterning (Estelle 1998;Friml and Palme 2002;Ikeda et al 2009;Forestan and Varotto 2012). It has reported that rice OsPIN1 gene expressed in root cap, OsPIN1b, OsPIN1c and OsPIN9 predominantly expressed in stele and OsPIN1b, OsPIN1c, OsPIN5a and OsPIN5b found to be expressed in meristem tissues (Wang et al 2009b). …”
Section: Introductionmentioning
confidence: 99%